Unknown - Thusky, Shaynah Decontie (Canada, 2011)
Two years ago, Maisy and Shannon disappeared from the Kitigan Zibi community in Quebec. The media did not cover the event, despite the fact that this situation has become alarmingly common in many communities.
Verzio Film Festival Submission
Keywords: Canada